30.0k views
2 votes
Simplify this radical.
Square root of x to the 13th power

User Phyl
by
4.7k points

2 Answers

2 votes

Answer:


\large\boxed{\sqrt{x^(13)}=x^6√(x)}

Explanation:


\sqrt{x^(13)}=\sqrt{x^(12+1)}\qquad\text{use}\ a^na^m=a^(n+m)\\\\=\sqrt{x^(12)x^1}\qquad\text{use}\ √(ab)=√(a)\cdot√(b)\\\\=\sqrt{x^(12)}\cdot√(x)=\sqrt{x^(6\cdot2)}\cdot√(x)\qquad\text{use}\ (a^n)^m=a^(nm)\\\\=√((x^6)^2)\cdot√(x)\qquad\text{use}\ √(x^2)=|x|\\\\=|x^6|√(x)=x^6√(x)\ \text{because}\ x^6\geq0

User Ron Serruya
by
5.1k points
4 votes

Answer:

x^6
√(x)

Explanation:

we have:


\sqrt{x^(13)}

we can write:


\sqrt{x^(13)} :
\sqrt{x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x}

we know:


\sqrt{x^(2)} = x

so we have:


\sqrt{x^(13)} =
\sqrt{x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x}

we have:


\sqrt{x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x^(2)*x}=


x^(6) √(x)

User JOV
by
4.7k points